Review Literatur: DINAMIKA PENGEMBANGAN PERKEBUNAN SAGU BERKELANJUTAN BERBASIS KEARIFAN LOKAL - Partini, Partini; Noer, Melinda; Suliansyah, Irfan; Devianto, Dodi (JURNAL AGRIBISAINS, 2023)
Sago is a native Indonesian plant that has the potential to be developed as a food and non-food source because it has several advantages, namely high starch content, resistance to climate change, being able to grow and adapt to marginal environments. Sustainability of sago plantation management must meet environmental, economic, social and institutional aspects. The purpose of this study is to identify the dynamics in the development of sago plantations and forms of local wisdom that can support the development of sustainable sago plantations. The research method used is a qualitative approach with Systematic Literature Review (SLR). The results of article review show that the development of sago plantations faces constraints of low productivity and unsustainability from social, economic, environmental culture and institutional aspects. Meanwhile in the community there are local wisdom sago management practices that have a positive effect on the five aspects of sustainability. However, previous study is still partial and does not focus on the sago plantation sector. Research questions about how to develop sustainable sago plantations based on comprehensive local wisdom is the novelty that are offered to be answered in future research.